Hierarchy and the size of a firm - Tobias Hiller (International Review of Economics, 2021)
In this note, we apply weighted hierarchical games of cooperative game theory to the problem of optimal firm size of the firm. In particular, we analyze the influence of production technology on the size of the firm. Our note enhances previous approaches using a permission structure with equally strong relationships between predecessor and direct successors.
Keywords: C71; L25; 330; Cooperative game theory; Hierarchy